Some issues in Malaysia agricultural development strategies - Arshad, Nasaruddin; Mustapha, Zulkifly (Universiti Utara Malaysia, 1986)
Emphasis is often placed on agricultural development as a vital component of the Malaysian economic strategies. The outcomes of this policy, without the risk of over emphasised, have been encouraging in terms of agricultural contribution to the gross national product, foreign exchange earnings, and national employment. Agricultural development also increases income of the rural poor significantly. Despite this, the success of agricultural development strategy is not without shortcomings, at least in terms of conflicts arised from multiobjectives of the development policy. This article goes some way towards, identifying some of the conflicts arised from the previous and present agricultural development strategies.Based on these conflicts, it discusses general areas that should be pursued to successfully implement the agricultural development strategies.